PROFIL PEMECAHAN MASALAH SISWA DALAM MENYELESAIKAN SOAL TURUNAN FUNGSI ALJABAR DITINJAU DARI KEMEMPUAN MATEMATIKA PADA KELAS XI MIA 2 SMA NEGERI 1 SIRENJA: Students Problem Solving Profile In Solving Algrebaic Finction Derivative Problems In Terms Of Mathematics Ability In Class XI MIA 2 SMA Negeri 1 Sirenja - Pratiwi, Anggun; Ismaimuza, Dasa; Murdiana, I Nyoman (Jurnal Elektronik Pendidikan Matematika Tadulako, 2024)
This study aims to describe the Profile of Students’ Problem Solving in Completing Mathematics Problem on the of Derivatived Algebra Function Assessed From Mathematical Ability or the Grade XI Students of SMA Negeri 1 Sirenja. This study uses a qualitative method based on the problem solving steps proposed by Polya. The results of this study indicate that the subject of FM students with high math ability, LF students with moderate math ability, and NAA students with low math ability in solving problems derived from algebraic functions are as follows: (1) the stage of understanding the problem of the subject, the subject understands the problem given well, the subject identifies the existing information as what is known and what is ordered by the question correctly, (2) the stage of making a problem solving plan FM subject has a problem-solving plan using the formula , and for LF and NAA subjects on (M1 1, M2 1) the plan used is to multiply the value of the function f (x) first, for (M1 2, M2 2) the subject uses the formula , (3) the stage of implementing the problem understanding plan of the FM subject carries out the plan according to what was previously planned and obtains the correct solution, the LF and NAA subjects also carry out the plan according to the plan previously planned but in (M1 1 and M2 1) the settlement process is lacking correct but obtains the correct final result, whereas in (M1 2 and M2) the subject gets the correct solution, (4) the stage of re-checking the results of the work of the subject FM, LF, and NAA to re-examine the results of their work.